Dias de visita: uma sociologia da punição e das prisões em Itirapina - Silvestre, Giane (2011)
The aim of the present work is to understand the transformations in São Paulo State prisons policies in the last three decades, from a case study on the city of Itirapina, located in the central region of the state. There are two prisons facilities installed at different moments, the city of Itirapina presents peculiarities in the prisons scene, therefore it is possible to observe the existence of two prisons implanted with distinct models and philosophies operating simultaneously. The first prison was founded in 1978, still under Brazilian s military dictatorship rules, and the second was founded in 1998 in a democratic context. The research realized a literature review on studies on violence, crime, punishment and social control, both globally and locally. The empirical research consisted of an archival research on local media reports, interviews with shopkeepers, prison agents and ethnography of the visit days with prisioners wives and on the meetings of the Itirapina s Community Security Council. It was possible to observe that the subjects involved with prison s daily life in the city of Itirapina, have a different perception and relationship with each one of the prisons installed, thus showing the coexistence of two distinct models of prisons policies where global perspectives cross local instances. The analysis point out a change in São Paulo State incarceration policies directives, in line with the changes that occurred worldwide, where the ideal of punishment as a social reinsertion element of prisoners, fell into decline, giving way to the policies of accelerated imprisonment turned to the control and management of prisoners, beyond the expansion of the prison system to the countryside municipalities. The presence of prisons impacts the local sociality, reordering the moral life and denying integration to the prisoners relatives in city life.